Accessibility, Availability, and Potential Benefits of Psycho‐Oncology Services: The Perspective of Community‐Based Physicians Providing Cancer Survivorship Care. (June 2017) - Zimmermann‐Schlegel, Verena; Hartmann, Mechthild; Sklenarova, Halina; Herzog, Wolfgang; Haun, Markus W.
Abstract: Background: As persons of trust, community‐based physicians providing survivorship care (e.g., general practitioners [GPs]) often serve as the primary contacts for cancer survivors disclosing distress. From the perspective of physicians providing survivorship care for cancer patients, this study explores (a) the accessibility, availability, and potential benefits of psycho‐oncology services; (b) whether physicians themselves provide psychosocial support; and (c) predictors for impeded referrals of survivors to services. Methods: In a cross‐sectional survey, all GPs and community‐based specialists in a defined region were interviewed. In addition to descriptive analyses, categorical data were investigated by applying chi‐square tests. Predictors for impeded referrals were explored through logistic regression. Results: Of 683 responding physicians, the vast majority stated that survivors benefit from psycho‐oncology services (96.8%), but the physicians also articulated that insufficient coverage of psycho‐oncology services (90.9%) was often accompanied by impeded referrals (77.7%). A substantial proportion (14.9%) of physicians did not offer any psychosocial support. The odds of physicians in rural areas reporting impeded referrals were 1.91 times greater than the odds of physicians in large urban areas making a similar report (95% confidence interval [1.07, 3.40]). Conclusion: Most community‐based physicians providing survivorship care regard psycho‐oncology services as highly beneficial. However, a large number of physicians report tremendous difficulty referring patients. Focusing on those physicians not providing any psychosocial support, health policy approaches should specifically (a) raise awareness of the role of physicians as persons of trust for survivors, (b) highlight the effectiveness of psycho‐oncology services, and (c) encourage a proactive attitude toward the assessment of unmet needs and the initiation of comprehensive care. Implications for Practice: Community‐based physicians providing survivorship care for cancer patients regard psycho‐oncology services as a highly reasonable and beneficial addition to medical care. In light of insufficient local coverage with services, difficulties with seamless referrals constitute a major challenge for physicians. Apart from emphasizing the effectiveness of psycho‐oncology services and proactive attitudes toward the assessment of unmet needs, future policies should focus on the integration of medical and psychosocial follow‐up of cancer survivors, especially in rural areas. Abstract : By applying an exploratory cross‐sectional survey, this study evaluates current referral practices of a large sample of community‐based physicians caring for post‐treatment cancer survivors. The accessibility, availability, and benefits of psycho‐oncology services are explored, as well as who provides psychosocial support and predictors for impeded referral to services.